Cutaneous Meningioma: A Cytomorphological Diagnosis - Kishore, Manjari (Indian Dermatol Online J, 2017)
Cutaneous meningiomas are rare tumors. These are ectopic meningothelial cells located in the dermis and subcutis, and are usually seen on the scalp. Here, we report the case of a 40-year-old woman who presented with a slowly growing asymptomatic mass over the scalp in the right parieto-occipital region. The lesion was firm, adherent to underlying structures, and covered by normal appearing skin. The cytomorphological features along with histological and immunohistochemical studies showing positivity for epithelial membrane antigen, Vimentin, and S100 helped in making a definitive diagnosis of cutaneous meningioma. No evidence of intracranial meningioma was noted in contrast-enhanced computed tomography of the brain.